Design and construction of an efficient multicopter - Tan, Xavier Khen Leong (2018)
Unmanned Aerial Vehicles (UAVs), are getting increasingly popular around the world over the years and its industry to-date is still growing and it is getting much closer to consumer level. It has attracted attention from hobbyists, the military and our average consumer. The demand is not likely to stagnate or decrease any time soon. The capabilities of these UAVs range from deliveries, to site inspections, to racing against each other, also known as First Person View (FPV) racing, aerial photography and videography. These UAVs are built in different shapes and sizes for its intended applications. There are many different configurations for the UAV such as the Hexacopter, the Quadcopter and Helicopters depending on its application. The quadcopter will be the focus of this project due to its simplicity in design and its popularity over the others. This report will document the hardware selection of the components of the quadcopter, the construction process and some tests to find out and evaluate the efficiency of the quadcopter. Each of these components will be presented in theory and analysis of how they affect the actual flight of thequadcopter. Endurance of the quadcopter will be the key point of this project.